Finding Refuge in King Lear: From Brexit to Shakespeare’s European Value - O’Neill, Stephen (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
This article considers how Shakespeare’s King Lear has become a Brexit play across a range of discourses and media, from theatre productions and journalism to social media. With its themes of division and disbursement, of cliff edges and tragic self-immolation, Lear is the Shakespearean play that has been turned to as metaphor and analogy for the UK’s decision following the 23 June 2016 referendum to leave the European Union. Reading this presentist application of Shakespeare, the article attends to Shakespeare as itself a discourse through which cultural ideas, both real and imaginary, about Brexit and the EU are negotiated. It asks how can we might remap Lear in this present context―what other meanings and histories are to be derived from the play, especially in Lear’s exile and search for refuge, or in Cordelia’s departure for and return from France? Moving from a consideration of a Brexit Lear to an archipelagic and even European Lear, this article argues that Shakespeare is simultaneously a site of supranational connections and of a desire for values of empathy and refuge that reverberate with debates about migration in Europe.